2015
DOI: 10.1159/000441606
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7)/Mas Signaling Inhibits Lipopolysaccharide-Induced ADAM17 Shedding Activity and Apoptosis in Alveolar Epithelial Cells

Abstract: A disintegrin and metalloproteinase (ADAM) 17, constitutively expressed in alveolar epithelium, is the pivotal shedding enzyme mediating acute lung inflammation. On the other hand, angiotensin (Ang)-(1-7)/Mas signaling has been shown to improve acute respiratory distress syndrome and protect alveolar epithelial cells from apoptosis. In this study, we explored the effect of Ang-(1-7)/Mas signaling on the expression and activity of ADAM17 and assessed its impact on apoptosis in lipopolysaccharide (LPS)-treated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Since both compounds activate the shedding of ADAM17 substrates, we suggest that it is possible that two of the common activated phosphoproteins—c-Jun and Stat5a/b—could explain these effects. In fact, it has been observed that the modulation of c-Jun or Stat5a activation also modulates TNF shedding elicited by BPA and NP in cancer cell lines [72,73,74]. However, it remains to be investigated whether the activation of the phosphoproteins observed in the present study is due to a direct activation of BPA and NP or whether this activation is achieved indirectly, by the shedding and auto/paracrine activation of cognate receptors, which seems to be the case of BPA [69].…”
Section: Discussionmentioning
confidence: 99%
“…Since both compounds activate the shedding of ADAM17 substrates, we suggest that it is possible that two of the common activated phosphoproteins—c-Jun and Stat5a/b—could explain these effects. In fact, it has been observed that the modulation of c-Jun or Stat5a activation also modulates TNF shedding elicited by BPA and NP in cancer cell lines [72,73,74]. However, it remains to be investigated whether the activation of the phosphoproteins observed in the present study is due to a direct activation of BPA and NP or whether this activation is achieved indirectly, by the shedding and auto/paracrine activation of cognate receptors, which seems to be the case of BPA [69].…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known concerning the physiological roles of the ACE2/ANG-(1-7)/MAS axis in the lung, it appears to be critically involved in pathophysiological processes in this organ. ANG-(1-7) has been reported to reduce lung inflammation, fibrosis, and pulmonary arterial hypertension (92,310,333,338,364,445,449,576). MAS has been detected in the epithelium and bronchial smooth muscle, suggesting sites where the beneficial actions of ANG-(1-7) may occur (148,338).…”
Section: E Lungmentioning
confidence: 99%
“…ulates cell survival, inhibiting alveolar epithelial cell (AEC) apoptosis, a critical event that initiates and propagates lung fibrotic disease. It decreases AEC apoptosis through pathways including the inhibition of JNK activation (312), reduction of endoplasmic reticulum (ER) stress-induced apoptosis (549), inhibition of LPS-induced ADAM17 shedding activity (333), and the upregulation of MAPK phosphatase-2 (219). Altogether, these findings indicate that this peptide may hold therapeutic potential in the treatment of lung fibrosis.…”
Section: E Lungmentioning
confidence: 99%
“…However, little is known about the potential roles of ACE2-Ang-(1-7)-Mas in apoptosis, and its precise method of regulation in any organ system. Various studies have demonstrated that Ang-(1-7) regulates alveolar epithelial cell survival by inhibiting c-Jun N-terminal kinase phosphorylation and apoptosis through the Ang-(1-7) receptor Mas (17)(18)(19)(20). Gaddam et al (12) identified that the Ang II to Ang-(1-7) ratio increased in the pancreas, suggesting dysregulation of RAS in AP as evidenced by altered Ang II/Ang-(1-7) levels induced by the imbalance of ACE/ACE2 activity.…”
Section: Introductionmentioning
confidence: 99%